Left atrial function after standalone totally thoracoscopic left atrial appendage exclusion in af patients with absolute contraindication to oral anticoagulation therapy. (4th February 2022) - Tedoldi, F; Branzoli, S; D"onghia, G; Fanti, D; Sarao, E; Guarracini, F; Quintarelli, S; Graffigna, A; Bonmassari, R; La Meir, M; Monaco, C; De Asmundis, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Left atrial appendage (LAA) is the source of more than 90% of thrombi in patients with atrial fibrillation (AF). The Totally Thoracoscopic (TT) LAA exclusion with epicardial clip has become a safe and effective procedure, but the effect on left atrial (LA) function remains unknown. Purpose: The aim of this study was to assess the effect of TT LAA exclusion on LA function. Methods: 20 patients (15 males) with non-valvular AF and contraindication to oral anticoagulation therapy (OAT) or antiplatelet therapy underwent standalone TT LAA exclusion with the Atriclip Pro II device. All patients were screened preoperatively with 3D CT scan, trans-esophageal echocardiography, spirometry and cerebrovascular doppler ultrasound. Intraoperative Atriclip Pro II positioning and LAA exclusion were guided and confirmed by trans-esophageal echo. To objectify LA function, transthoracic echocardiography with 2D Speckle tracking was performed before surgery, at discharge and at 3-month follow-up. All patients were not on anticoagulation nor antiplatelet therapy at the time of surgery, at discharge and at control visit. Results: Baseline characteristics are reported in Table I. There were no major complications during the procedures. One non cardiovascular death, one minor stroke and 4 hospitalizations occur at 1-year follow up. The reservoir LA function considering the strain measurements dramatically decreased few days after the procedure and it recovered at 3-month follow-up compared to baseline, even though the LA volume is augmented (Table II). Furthermore, NT pro-BNP increased and ventricular strain decreased significantly after the procedure recovering over time. Conclusion: TT LAA exclusion with Atriclip Pro II device is a safe and effective procedure in preventing AF related stroke in patients with contraindication to OAT. Our findings suggest that the LAA epicardial clip impairs immediately the reservoir LA function that recovers over time.